'Rationalized incrementalism'. How behavior experts in government negotiate institutional logics. Issue 2 (2nd April 2020) - Feitsma, Joram
ABSTRACT: Public policy design takes place in a complex 'policy swamp' that is not easily analyzed, let alone controlled. Nonetheless, recent scientific advances in understanding human behavior have led some to believe there is a way out of this swamp. A 'Behavioural Insights' movement has emerged, pushing a seemingly neo-rationalist strategy that clashes with the hitherto incrementalist strategy of policy-making. This article investigates how upcoming behavior experts in Dutch government grapple with this clash, based on long-term ethnographic fieldwork. The article points out that these behavior experts, despite their clear-cut rationalist impression, in the backstage take on the challenge of negotiating competing institutional logics.